Bioethical and biojuridical approach to the genetic counselling for Alzheimer's disease. - Garofalo, Lorella; Mele, Vincenza (Medicina e Morale, 2001)
The article, first of all, analyses the ethical aspects linked to the predictive medicine regarding the Alzheimer's disease (AD). Besides, the authors dwell upon the ethical significance of the role of the genetic counselling, particularly regarding the situation in which asymptomatic subjects to risk for AD ask for an available predictive genetic test. In this case the ethical reflection is mostly problematic and involves different aspects: the use of safe and effective test in health care organisations (HCOs) with adequate standards of quality; the issues related to counselling (patient's autonomy, informed consent, psycho-social care); the professional education of the health care workers. Moreover, the authors show and comment the data of an investigation about the predictive test for AD and the HCOs where the test is performed. Finally, the ethical and legal role of the health care professional is underlined, particularly about the elaboration of specific guidelines and the protection of privacy of patient's genetic data.